EXAMINATION OF 5TH AND 6TH GRADE SCIENCE TEACHING PROGRAMS AND SCIENCE TEACHER TRAINING SYSTEMS OF TURKEY AND IRELAND - Hikmet SÜRMELİ and Ahmet Şahin ONGUN (International Journal of Eurasia Social Sciences, 2017)
In this study, it was aimed to compare science education curriculum of Turkey and Ireland in terms of vision, aim, contents. Document analysis, one of the qualitative research methods, was used for this study. Related to visions, it was found that both of the curriculums were aimed to train the target students as scientifically literate. Related to the aims, it was determined that both of the curriculums applied student centered learning approaches. Related to learning achievements, it was found that, in the science curriculum in Turkey were more in number comparing with the science curriculum in Ireland. The skills in the science curriculum in Ireland have been planned in more detailed comparing with the skills in the science curriculum in Turkey. In science curriculum in Ireland, it was emphasized developing students in the stages of scientific studies and design. Related to science teacher training systems, in this study, it was revealed some similarities and differences. Results of this study showed that, both of the countries science education curriculums were similar in terms of visions and aims, whereas, science teacher training systems were showed some differences in terms of contents. Based on these results, it can be suggested to decrease the number of existing achievements in the Curriculum of Turkish Science Education.